The first hot pluggable 2.5 gigabytes DWDM transceiver in an SFP form factor. - Priyadarshi, Sunil (IEEE Communications magazine)
For the first time, a hot pluggable 2.5 Gb/s DWDM transceiver with 100 GHz spacing in an SFP form factor has been presented. We demonstrate transmit wavelength drift of plusmn9 pm and optical output power stability of 0.2 dB over an operating case temperature range of -5degC to 70 degC. The minimum receive sensitivity was -33.2 dBm for back-to-back, -32.6 dBm after transmission over 80 km of standard SMF, and -28 dBm for an OSNR level of 16 dB at a BER of 1 times 10-10.